D,the LITERASI DIGITAL DAN INKLUSI DIGITAL: KEBIJAKAN INFORMASI DAN PERPUSTAKAAN UMUM - Sya Laisa Amara; Shintia Rahayu Safitri; Sulpani, Naila tunnada (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
This research is entitled "digital literacy and digital inclusion: Information Policy and Public Libraries". The purpose of this study is to find out how students understand the importance of literacy and approaches to digitalization related to information policy and public libraries. This study uses descriptive quantitative research methods by distributing questionnaires to students at UIN Syarif Hidayatullah Jakarta. Informants in this study were active students at UIN Syarif Hidayatullah Jakarta. The data collection technique used in this research is the distribution of questionnaires containing questions about digital literacy and digital inclusion. There are four aspects of digital literacy competence according to Paul Gilster that are used in this study. The results obtained are active students at UIN Syarif Hidayatullah Jakarta in general master several aspects of digital literacy competence, especially in internet searching abilities, namely using search engines in information search, understanding the internet as a source of information and liaison, and utilizing the internet to carry out several activities. Not all students can understand how hyperlinks work and know the difference between the information on the internet and print media in terms of hypertextual navigation capabilities, and also about the meaning of hypertext and how it works. In evaluating the content, students are also not yet able to understand the characteristics of websites that are used as references, cross-check the information they get, and use FAQs on a website to help them obtain information. Students can use keywords to make it easier to search for information on aspects of knowledge assembly.